Temperature Control Technology for Construction of Jinsha River Bridge - Hui-Wu Jin (Hindawi Limited, 2021)
The key problem of mass concrete temperature control is to effectively control the maximum temperature inside concrete, the temperature difference between inside and outside concrete, and the temperature difference between surface and environment. The size of the main tower cap of No. 3 Jinsha River Bridge is 37 m × 23.5 m × 5.5 m, and the cubic volume of concrete reaches 4782.3 m3, which is poured in two times. In order to ensure construction quality of mass concrete structure, prevent the large mass concrete temperature stress, through the numerical simulation of the temperature control and optimization scheme, by optimizing the mixture ratio design, reducing the temperature of concrete pouring into the mold, cooling water cycling, insulation keeping in good health and a series of measures to effectively achieve the control goal, and eliminating the temperature cracks. The measured data show that the maximum temperature inside concrete, the temperature difference between inside and outside, and the temperature difference between surface and environment are qualified, but the temperature difference control of cooling water inlet and outlet has hysteresis effect, and the temperature difference between inlet and outlet will be greater than 10°C, which should be noticed.